Examination of membrane protein expression in Paracoccus denitrificans by two-dimensional gel electrophoresis - Bouchal, Pavel; Kucera, Igor (Journal of basic microbiology, 2004)
The well-known metabolic versatility of the soil bacterium Paracoccus denitrificans poses a challenge for modern proteomic approaches. We describe here improved preparation conditions that allow good separation and quantitative analyses of hundreds of membrane or periplasmic proteins. To illustrate this optimized procedure, the results of a screening for membrane proteins associated predominantly with aerobic or anaerobic (denitrifying) modes of growth are presented.
Keywords: membránové proteiny; anaerobióza; proteomika; Membrane Proteins; Gene Expression Regulation, Bacterial; Electrophoresis, Gel, Two-Dimensional; aerobióza; Aerobiosis; bakteriální geny; Anaerobiosis; Bacterial Proteins; Periplasm; kyslík; Proteomics; Gene Expression; Paracoccus denitrificans; periplazma; 2D gelová elektroforéza; regulace genové exprese u bakterií; Genes, Bacterial; exprese genu; Oxygen; bakteriální proteiny